Microbial oxidation of dodecane and tridecane into a,w-dicarboxylic acids using recombinant Yarrowia lipolytica - Diedericks, Danie (Centre for Bioprocess Engineering Research, 2014)
Includes bibliographical references (leaves 137-150).